1966
DOI: 10.1021/bi00873a034
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the Nucleotide Arrangement in Deoxyribonucleic Acids. XI. Selective Removal of Cytosine as a Tool for the Study of the Nucleotide Arrangement in Deoxyribonucleic Acid*

Abstract: When calf thymus deoxyribonucleic acid (DNA) is treated with nitrous acid at pH 3.35, com-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

1968
1968
2005
2005

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Deamination products of cytosine and adenine may be repaired (29,30), but the extreme instability of xanthine in DNA (31) leads to its rapid depurination (32). The rate of deamination of guanine may normally be so slow, and the half-life of xanthine may be so short that no excision repair system evolved.…”
Section: Resultsmentioning
confidence: 99%
“…Deamination products of cytosine and adenine may be repaired (29,30), but the extreme instability of xanthine in DNA (31) leads to its rapid depurination (32). The rate of deamination of guanine may normally be so slow, and the half-life of xanthine may be so short that no excision repair system evolved.…”
Section: Resultsmentioning
confidence: 99%
“…For this reason, it is not possible to determine the rate of adenine deamination in double-stranded DNA by prolonged incubation of DNA solutions at temperatures below the fm, because significant depurination with accompanying chain breakage and generation of single-stranded sequences would occur before detectable amounts of hypoxanthine were formed. Since a hypoxanthine-deoxyribose bond is slightly weaker than an adenine-deoxyribose bond in DNA (Shapiro & Chargaff, 1966), some of the deaminated adenine residues were released from the DNA by depurination during the longest incubations. In the standard procedure, the whole DNA solution was analyzed for the presence of hypoxanthine after heat treatment.…”
Section: Resultsmentioning
confidence: 99%
“…Deoxyinosine can be generated in DNA from deoxyadenosine by deamination either spontaneously or in the presence of nitrous acid. 5) Point mutations are thought to be induced in many cases by modification of a base in DNA by a mutagen and subsequent misincorporation of an incorrect deoxynucleoside triphosphate at the site opposite to the modified base catalyzed by DNA polymerase. The base pairing properties of hypoxanthine had been studied, and results had shown that hypoxanthine in oligonucleotides forms a stable base pair with an adenine or cytosine residue in the opposite strand.…”
mentioning
confidence: 99%